Leibniz and the Natural World - Phemister, Pauline. author. aut Link
XVI, 298 p.
Keywords: In the present book, Pauline Phemister argues against traditional Anglo-American interpretations of Leibniz as an idealist who conceives ultimate reality as a plurality of mind-like immaterial beings and for whom physical bodies are ultimately unreal and our perceptions of them illusory. Re-reading the texts without the prior assumption of idealism allows the more material aspects of Leibniz's metaphysics to emerge. Leibniz is found to advance a synthesis of idealism and materialism. His ontology posits indivisible, living, animal-like corporeal substances as the real metaphysical constituents of the universe; his epistemology combines sense-experience and reason; and his ethics fuses confused perceptions and insensible appetites with distinct perceptions and rational choice. In the light of his sustained commitment to the reality of bodies, Phemister re-examines his dynamics, the doctrine of pre-established harmony and his views on freedom. The image of Leibniz as a rationalist philosopher who values activity and reason over passivity and sense-experience is replaced by the one of a philosopher who recognises that, in the created world, there can only be activity if there is also passivity; minds, souls and forms if there is also matter; good if there is evil; perfection if there is imperfection.